1995
DOI: 10.1103/physrevb.51.9943
|View full text |Cite
|
Sign up to set email alerts
|

Nonresonant carrier transport through high-field domains in semiconductor superlattices

Abstract: The actual Beld distribution in superlattices under electric field domain formation is investigated by photoluminescence and Raman spectroscopy. Prom the measured subband spacings, we determine the magnitude of the Beld that corresponds to resonant alignment of subbands in adjacent wells.The electron occupation of higher subbands is probed by photoluminescence (PL) measurements. Comparing the results of higher subband PL and the current-voltage characteristics, it is shown that the high-Beld domain is always n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1

Year Published

1995
1995
2005
2005

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 29 publications
2
30
1
Order By: Relevance
“…1B which exhibits the usual sequence of branches [1,2]. In contrast to previous theoretical results the maximal current of the branches (90 µA) is significantly lower than the height of the first resonance.…”
Section: Resultscontrasting
confidence: 80%
See 1 more Smart Citation
“…1B which exhibits the usual sequence of branches [1,2]. In contrast to previous theoretical results the maximal current of the branches (90 µA) is significantly lower than the height of the first resonance.…”
Section: Resultscontrasting
confidence: 80%
“…This may yield complicated current-voltage characteristics exhibiting many branches due to the formation of domains with different electric fields inside the sample (see, e.g., [1] and references therein). These experimental features could be qualitatively reproduced by theoretical models combining the rate equations for the transport between the wells and Poisson's equation [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Results for the superlattice studied experimentally in [123,124] (9 nm wide GaAs wells, 4 nm AlAs barriers, doping density N D = 1.5 × 10 11 /cm 2 , cross section A = 1.13 × 10 −4 cm 2 ) are shown in Fig. 11.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the Gunn diode, semiconductor superlattices frequently exhibit the formation of stable stationary domains which lead to a characteristic saw-tooth pattern in the currentvoltage characteristic (see Fig. 21a) as observed by many different groups [16,17,123,124,[170][171][172][173][174]. (See also [175,176] for domain formation in a parallel magnetic field.)…”
Section: Formation Of Field Domainsmentioning
confidence: 99%
“…17 The effects of the Zener breakdown under a relatively strong bias on the WSL spectra and nonlinear transport, ͑i.e., the Bloch oscillation͒ resulting in negative differential resistance ͑NDR͒, were later discussed by many authors. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Hereafter, the resonant Zener tunneling between different energetically aligned subbands will be termed as Zener resonance or WSL resonance. Delocalized electron states in coupled WSL in biased SLs were first observed by photocurrent spectroscopy along with the measurement of the currentvoltage characteristics by Schneider et al 18 They observed the delocalization of electrons and anticrossing behavior ascribable to the nearest-and the second-nearest-neighbor resonant couplings induced by the Zener resonance.…”
Section: Introductionmentioning
confidence: 99%